Thermal Chladni plate experiments to reveal and estimate spatially dependent vibrothermal source. Issue 2 (3rd April 2019) - Rodriguez, Samuel; Meziane, Anissa; Pradère, Christophe
ABSTRACT: In viscoelastic media, mechanical energy is partially converted to thermal energy. Thus, the vibration of a structure implies that there are thermal heat sources due to mechanical dissipation induced by acoustical vibration. The heat sources are directly linked to the stress and strain tensors. In the present work, a rectangular plate made of viscoelastic material is studied from both mechanical and thermal points of view. Three different experiments are applied to the specimen: classical Chladni plate, laser Doppler velocimetry and infrared surface temperature measurements. The specimen is fully characterized in terms of mechanical and thermal properties in order to simulate the vibrothermal experiment using 3D finite-element modeling. The dynamic temperature field is thus obtained both experimentally and numerically. An inverse thermal processing is proposed in order to quantitatively retrieve thermal heat source distributions relative to the acoustical field. In this paper, numerical simulations are used to validate the inverse processing, and the first results applied to the experimental data are depicted. It is shown that the simulation and experiments are quantitatively in good agreement. For a given resonance frequency, Chladni experiments allow for the retrieval of displacement mode shapes, whereas infrared thermography allows for the retrieval of heat source mode shapes.